LEGAL FOUNDATIONS OF INHERITANCE AND HEIRSHIP - Azirbaev Salamat Kuanishbaevich, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  article  provides  a  detailed  analysis  of  inheritance  and  the  fundamental principles governing it. The legal basis of inheritance is examined in accordance with inheritance law, including key concepts such as wills and testamentary succession.